2020
DOI: 10.21608/adjg.2020.13117.1148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Root Changes and Bone Density Accompanying Different Methods of Accelerated Orthodontic Tooth Movement

Abstract: Purpose: This study was carried out to evaluate root surface changes and bone density accompanying two different methods of accelerated orthodontic tooth movement by Cone beam computed tomography (CBCT). Patients and methods: The present study was applied to twenty patients. With bimaxillary dento-alveolar protrusion or Angle Class II Division 1 malocclusion. The line of treatment was the extraction of the upper first bicuspids and then cuspid distalization. The patient's sample was divided into two equal grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…[ 5 ] Hence, numerous techniques are used to decrease the time needed for orthodontic treatment time. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 5 ] Hence, numerous techniques are used to decrease the time needed for orthodontic treatment time. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Currently, very fewstudies have reported the changes in bone density after performing MOP using CBCT. [ 5 13 15 16 ] The use of CBCT and micro CT in orthodontic research has provided great insights into alveolar bone density changes incident to tooth moving forces. [ 17 ] CBCT can be used in orthodontic research to measure alveolar bone density, width, and treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation